Rickettsial Diseases in the Mediterranean Basin: an Evolving Clinical and Epidemiological Challenge - Giulio D’Agati; Luca Pipitò; Chiara Iaria; Claudia Colomba; Antonio Cascio (Current Tropical Medicine Reports, 2026)
Abstract Purpose of Review Rickettsial diseases represent a major cause of arthropod-borne febrile illness in the Mediterranean basin, where climatic conditions, vector ecology, and close human–animal interactions promote the circulation of a wide diversity of Rickettsia species. In recent years, advances in microbial genomics and molecular diagnostics have substantially refined rickettsial taxonomy, clarified phylogenetic relationships across the Spotted Fever, Typhus, and Transitional Groups, and enhanced recognition of emerging pathogens. This narrative review provides an updated synthesis of rickettsial infections in the Mediterranean region, integrating microbiological, genomic, epidemiological, clinical, diagnostic, and therapeutic evidence. Recent Findings Mediterranean rickettsioses comprise a heterogeneous group of tick- and flea-borne infections caused by both well-established pathogens, such as Rickettsia conorii , and increasingly recognized species including R. aeschlimannii , R. massiliae , R. monacensis , and R. felis . Genomic and phylogenetic studies have identified distinct clades and key virulence determinants involved in host-cell entry, intracellular survival, endothelial damage, and vector adaptation. Summary Rickettsial diseases in the Mediterranean basin are evolving in response to climate-driven vector expansion, increasing pathogen diversity, and improved molecular detection methods. Clinically, disease manifestations range from the classical fever–rash–eschar presentation to severe forms with neurological, renal, cardiac, pulmonary, and ocular involvement, as well as hyperinflammatory syndromes such as hemophagocytic lymphohistiocytosis. Molecular assays performed on eschar or skin samples provide the highest diagnostic yield during the acute phase, whereas serological testing is limited by delayed antibody responses and cross-reactivity. Early treatment with doxycycline remains the most effective therapeutic strategy, while evidence supporting alternative agents and management in special populations, including children and pregnant women, remains limited. Nonetheless, important gaps persist in diagnostic accessibility, epidemiological surveillance, and data from vulnerable populations. Integrating advances in microbiology, molecular epidemiology, and a One Health framework is essential to improve diagnosis, inform clinical decision-making, and reduce the burden of rickettsioses in the Mediterranean region.